Tanggung Jawab Negara Indonesia untuk Melindungi Hutan dalam Penyelengaraan Food Estate menurut Konvensi Keanekaragaman Hayati - Galih Maulana Azkiya; Irawati (Bandung Conference Series: Law Studies, 2024)
Abstract. Facing the challenges of food security, the Food Estate Program becomes a strategic step for Indonesia in addressing strategic food security challenges. The success of this program lies in the state's responsibility to protect forests, which often serve as crucial natural resources. In the management of forests, policies, regulations, and practices, this study evaluates the extent to which the country prioritizes forest sustainability in designing and implementing the Food Estate Program. In this approach, the research employs a normative juridical approach to analyze the Convention on Biological Diversity (UNCBD) through the results of its ratification in National Law as Law No. 5 of 1994. This approach utilizes qualitative methods, involving data collection from various sources such as legal regulations, legal documents, and court decisions. The research results are expected to provide a better understanding of the concept of forest protection responsibility for the implementation of the Food Estate according to the Convention on Biological Diversity. Additionally, this normative study is also expected to identify indications of violations related to land rights seizure and land use conversion carried out by the government and the government's responsibility for resolving the committed violations. In a practical context, this research is expected to offer in-depth information, recommendations, and insights for policymakers, practitioners, and researchers in designing sustainable national food strategies in Indonesia. Abstrak. Dalam menghadapi tantangan ketahanan pangan, Program Food Estate menjadi langkah strategis bagi Indonesia dalam mengatasi tantangan ketahanan pangan strategis. dalam keberhasilan program ini adalah tanggung jawab negara dalam melindungi hutan, yang sering kali menjadi sumber daya alam yang penting. kebijakan, regulasi, dan praktek pengelolaan hutan, studi ini mengevaluasi sejauh mana negara memprioritaskan keberlanjutan hutan dalam merancang dan menjalankan program Food Estate. Dalam pendekatan ini, penelitian menggunakan metode pendekatan yuridis normatif untuk menganalisis konvensi keanekaragaman hayati (UNCBD) melalui hasil ratifikasi Hukum Nasional menjadi UU NO.5 TAHUN 1994. Metode Pendekatan ini menggunakan cara kualitatif, melibatkan pengumpulan data dari berbagai sumber, seperti peraturan hukum, dokumen hukum, dan keputusan pengadilan. Hasil penelitian diharapkan dapat memberikan pemahaman yang lebih baik tentang konsep Tanggung jawab perlindungan hutan untuk penyelenggaraan food Estate menurut Konvensi Keanekaragaman Hayati. Selain itu, studi normartif ini juga diharapkan dapat mengidentifikasi adanya indikasi pelanggaran terkait perampasan hak atas tanah dan pengalih fungsi lahan yang dilakukan oleh pemerintah dan tanggung jawab dari pemerintah terhadap penyelesaian pelanggaran yang dilakukan. Dalam konteks praktis, penelitian ini diharapkan dapat memberikan informasi,rekomendasi dan wawasan yang mendalam bagi para pembuat kebijakan, praktisi, dan peneliti dalam merancang strategi pangan nasional yang berkelanjutan di Indonesia).